No evidence for active viral infection in unicentric and idiopathic multicentric Castleman disease by Viral-Track analysis - Ira Miller; Melanie D. Mumau; Saishravan Shyamsundar; Mateo Sarmiento Bustamante; Pedro Horna; Michael V. Gonzalez; David C. Fajgenbaum (Scientific Reports)
Abstract Castleman disease (CD) is a rare hematologic disorder characterized by pathologic lymph node changes and a range of symptoms due to excessive cytokine production. While uncontrolled infection with human herpesvirus-8 (HHV-8) is responsible for the cytokine storm in a portion of multicentric CD (HHV-8-associated MCD) cases, the etiology of unicentric CD (UCD) and HHV-8-negative/idiopathic MCD (iMCD) is unknown. Several hypotheses have been proposed regarding the pathogenesis of UCD and iMCD, including occult infection given the precedent established by HHV-8 infection. To investigate potential active infections in UCD and iMCD, we implemented Viral-Track, a computational method that identifies viral mRNA sequences from next-generation sequencing data. We applied Viral-Track to short sequencing reads from a cohort of UCD (n = 22), iMCD (n = 19), and controls (n = 86). While viral sequences for several unusual viruses were identified in individual CD patients,  sequences for the same virus were not found across multiple CD patients or they were not specific to CD samples and were also found in non-CD samples. These results suggest that active viral infection is unlikely to be a pathological driver of UCD or iMCD.